Climate compatible wetland-based sanitation for sustainable cities (Eco-Cities) in East Africa - Balthazar, Thomas Lugeiyamu; Shipin, Oleg V.; Pathirana, Assela; Visvanathan, C.; Shrestha, Sangam; Bill & Melinda Gates Foundation/UNESCO-IHE; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
This research was done to propose a Climate Compatible process design of a Wetland-Based Sanitation for sustainable Cities in East Africa cities namely in Dar es Salaam and Mombasa. Through completion of this study the inventory assessment ofexisting sanitation situation in the studied areas were done through related stakeholders. The results entails that out of all the surveyed existing wetland-based sanitation systems, 80% experience various forms of operational problems. These problems include blockages, seepage and cracks that prevented WBS from performing satisfactorily as conventional wastewater systems. The study also discovered that 78% of population in the surveyed areas were found not have access to piped sewerage, which is disproportionate if compared to the percentage of growing population. Lack of appropriate sewerage can facilitate the discharge of untreated or partially treated wastewater to the environment.Theefficiency removal of several wastewater parameters from Hacienda eco-city estate WBSsystem based on secondary data were conducted to verifyif thesystem is achieving climate compatibility criteria. The study revealed a successful performance of the existing WBSsystem forwastewatertreatmentwith respect to organic matter (BOD, NO3-N and NH3-N) with removal efficiency of 95, 78, and 86% respectively. The quality of effluent meet the admissible local standard for discharging in surface water courses with 29.7, 9.04 &12.96 mg/l respectively. It has beenconcluded that thewetland system is climatecompatible.Furthermore, Review to evaluate retrofitfeasibilitydesign proposal was carried basing on analyzed parameters,HRT of 15 hrs in the primary treatment were calculated also hydraulic loading rate (HLR)of 0.345 m/d and the wetland area of 591.74 m2 based on BOD respectively were obtained, finally the width and length of CW was calculated. The systemaim is to promote the paradigm shift towards low emission and climate resilient development pathway by supporting theregion to limit thegreenhouse gas (GHG) emissions and adapt to the impacts of climate changethrough wastewater management.Finally the author recommended that for the proposed WBSsystem to live upinitiatives are neededtomobilize resources and build alliances with all stakeholders and potential partners to promoteaffordable and appropriate wetland-based sanitation with an emphasis on reduction of greenhouse gases (GHGs) emissions, nutrients recycle and renewable energy productions so that mitigate climate change for the sustainable development of the future citiesin East Africa.
Thesis (M.Eng.) - Asian Institute of Technology - UNESCO-IHE, 2014
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Urban Water Engineering and Management at Asian Institute of Technology and the degree of Master of Science in Municipal Water and Infrastructure at the UNESCO-IHE
Keywords: City planning -- East Africa -- Environmental aspects; Climatic changes -- East Africa; Wetland -- East Africa -- Environmental aspects